Credit performance, risk management practices and profitability of commercial banks of Nepal - Basnet, Shahadev; Kamaljeet,; Pant, Sushil Kumar (A Bi-annual South Asian Journal of Research & Innovation, 2025)
The objective of this study is to assess the effect of Credit performance and Risk Management practices on the profitability of Nepalese commercial banks. Commercial banks play an important role in the financial system of the country but they are also highly prone to risks especially the credit risk which directly affect the stability and performance of the bank. Yet, there is a little agreement in the literature on the impact of credit risk management factors such as solvency and nonperforming loans (NPLs) on the banking performance of banks in Nepal, despite a number of empirical studies being conducted globally. In this context the present study aims to cover such void and to determine the effects of the CRM practices in operational efficiency and profitability measures such as the ROA and Esp. This study is descriptive and causal-comparative in methodology with a quantitative approach. Data were collected from secondary sources among which were annual reports of all twenty commercial banks of Nepal without exception along with some survey responses from bank officials, and stakeholders for the fiscal year 2081, Chaitra. Statistical techniques like correlation, regression and descriptive statistics were used to analyses financial rations and risk indicators. Nepal's commercial banks are well capitalized and profitable, but they are confronted by credit risk. Our average CAR is 12.7%, significantly higher than the regulatory minimum ensuring robustness particularly in a COVID-19 environment. The average net profit is Rs. 9.58 billion and net income is Rs. 7.19 billion, however, the profit is quite concentrated in a couple banks (Nabil Bank Ltd., Global IME Bank ltd., Nepal Investment Bank ltd.). Credit risk is still a worry, with an overall average Non-Performing Loan (NPL) ratio of 3.5%, but half of banks have between 4–6% NPLs, and only 20% stay below 2% NPLs. Correlation analysis reveals that CAR has a significantly negative relationship with NPL (-0.35) but NPL’s association to profit is weakly positive (0.22).